Kebijakan Pendidikan Jepang Di Indonesia Dan Implikasinya Terhadap Pendidikan Islam - Cindy Mahfudhotul Awwaliyah; Moh. Kusno; Difaa'atul Mutammimah (Pascasarjana Universitas Qomaruddin, 2025)
Japanese education is known for its disciplined, practical education system that focuses on improving the quality of individuals and groups. In Indonesia, there are several Japanese policies implemented, especially in terms of school management, learning methods and a culture of hard work. This study aims to analyze how the influence of Japanese education policies implemented in Indonesia on the Islamic education system, both from the positive side and the challenges. Using a library research approach, this study relies on literature study and policy analysis to understand how the Japanese education system is adapted to the Islamic education situation. The results show that concepts such as high discipline and active learning have a positive impact on teaching effectiveness in Islamic schools. However, there are challenges in maintaining a balance between the positive secular nature of Japanese education and the Islamic values that form the basis of Islamic education in Indonesia. Therefore, an adaptation strategy that considers the synergy between the two systems is needed so that Islamic education retains its identity while utilizing the principles of Japanese education to improve the quality of learning. This research provides insights for education stakeholders in formulating policies that are more contextual and inclusive for the advancement of Islamic education in Indonesia.